Functional Liquid Crystal Elastomers Based on Dynamic Covalent Chemistry. Issue 70 (13th October 2022) - Valenzuela, Cristian; Chen, Yuanhao; Wang, Ling; Feng, Wei
Abstract: The marriage of liquid crystal elastomers with dynamic covalent chemistry can be a new paradigm for the development of dynamic and intelligent polymers with versatile functionalities, which is of paramount significance for many emerging applications such as adaptive optics, soft robotics, bioinspired camouflage, 3D/4D printing technology and beyond. Read more in the Review by Wang, Feng et al. (10.1002/chem.202201957 ) Abstract : Dynamic covalent chemistry has been considered one of the most promising avenues toward dynamic and intelligent polymers with versatile functionalities. This review offers an account of recent breakthroughs in advanced liquid crystal elastomers based on dynamic covalent bonds, which can provide new insights into a new generation of "smart" applications such as soft robotics, 3D/4D printing, adaptive camouflage, and beyond.